Decreased mitochondrial hydrogen peroxide release in transgenic Drosophila melanogaster expressing intramitochondrial catalase. - Kwong, L.K.; Mockett, R.J.; Bayne, A.C.V.; Orr, W.C.; Sohal, R.S. (Archives of Biochemistry and Biophysics, 2000)
The objective of this study was to develop strategies for manipulating oxidative stress transgenically in a multicellular organism. Ectopic catalase was introduced into the mitochondrial matrix, which is the main intracellular site of H2O2 formation and where catalase is normally absent. Transgenic Drosophila melanogaster were generated by microinjection of a P element construct, containing the genomic catalase sequence of Drosophila, with the mitochondrial leader sequence of ornithine aminotransferase inserted upstream of the coding region. Total catalase activities in whole-body homogenates of 10-day-old flies from four transgenic lines were approximately 30-160% higher than those from the parental and four vector-only control lines. Expression of catalase in the mitochondrial matrix was confirmed by immunoblotting and catalase activity assays. Mitochondrial release of H2O2 was decreased by approximately 90% in the transgenic lines when compared to levels in vector-only controls. This in vivo system provides a novel model for examining the functional significance of decreased mitochondrial H2O2 release.